Arabic handwriting recognition: Challenges and solutions - Gumah, Mohamed E.; E., Schneider (2008)
Optical Characters Recognition (OCR) is one of the active subjects of research since the early days of computer science.Even if Arabic characters are used by more than a half a billion people; Arabic characters recognition has not received enough interests by the researchers.Little research progress has been achieved comparing to what has been done with Latin and Chinese.The cursive nature of the Arabic characters makes it more difficult to achieve a high accuracy in character recognition since even printed Arabic characters are in cursive form.This paper presents the main challenges (difficulties) researchers are facing and up to dated solutions(the common methods) are used for Arabic text recognition.